Frankenstein Rather Than Faust? The Decline of Limit-Surpassing Forces (ENTHYMEMA, 2017)
Giovanni Bottiroli’s article “Frankenstein Rather Than Faust?” aims to problematize and investigate further the challenge to the notion of «rigid identity» proposed by extant scholarship. In order to do so, Bottiroli dismantles a univocal understanding of «identity», bringing to light the polysemy and porosity intrinsic to this term. In order to do so, the author discusses here different modes of identity, concentrating on two in particular: coincidence and non-coincidence with oneself. Taking this distinction as his point of departure, Bottiroli applies these interpretative frameworks to two of the most significant figures of Western imagination, Frankenstein and Faust.